The effects of exercise and two pre-exercise fluid amounts on cognition - Backes, T. P. (Journal of Human Sport & Exercise, 2015)
Exercise is associated with elevated mood states and arousal. Observational studies support the claim that exercise can help individuals think more "clearly` with reports of improved mood and feelings of psychological well-being following exercise. However, laboratory studies have produced equivocal results. The purpose of this study is to examine the effect of exercise intensity and two likely pre-exercise fluid amounts consumed by euhydrated athletes on cognitive performance. Fifteen college age students were randomly assigned to either a 150 ml or a 500 ml fluid condition on the first test day and received the other fluid condition on the second test day. Prior to exercise subjects completed baseline computerized cognitive tests then began a treadmill protocol of three 6 min stages at increasing intensity after which subjects completed cognitive tests. A second treadmill portion started at 7.5 mph for 2 min then speed was increased 0.5 mph every 30 s until voluntary exhaustion and final cognitive testing was completed. Our results demonstrate a facilitation of cognitive function in response to exercise with the exception of the match to sample cognitive test which showed lack of facilitation of cognition in the 500 ml condition at moderate exercise. Our research contributes to the growing field of exercise and its effects on cognition. Specifically working memory cognitive tests showed facilitation with exercise. These results may be applicable to a typical exercising population since our study included a common exercise mode (treadmill) at moderate and high intensities and likely fluid amounts.